Dermoscopy of cutaneous granulomatous disorders: A study of 107 cases. Issue 1 (8th January 2023) - Kalantari, Yasamin; Peymanfar, Amir Abbas; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam; Etesami, Ifa
Abstract: Background: Cutaneous granulomatous disorders (CGDs) can share some features, but an accurate assessment of various findings and their pattern can be useful in differentiating them. In addition to common dermoscopic findings for CGDs, some peculiar dermoscopic characteristics can be helpful in distinguishing them. Objective: Herein, we aimed to evaluate dermoscopic findings in patients with CGDs and determine the dermoscopic criteria that could suggest the type of granulomatous disorder. Material and methods: A total of 107 cases including 75 (70.09%) males and 32 (29.90%) females with an established diagnosis of cutaneous leishmaniasis ( n = 49), cutaneous sarcoidosis ( n = 23), granuloma annulare (GA) ( n = 18), and tattoo granuloma ( n = 17) confirmed by clinical and pathological studies were included. Based on the previous studies available in the literature, we wrote a checklist containing dermoscopic features of CGDs. Afterward, two dermatologists independently reviewed all dermoscopic images for the presence or absence of each item on the checklist. Descriptive analysis, fisher exact, chi‐square, and t ‐test were used. The granulomatous disorders with larger sample sizes were selected for further analysis, including the univariate and conditional multivariate logistic regressions. Results: The most prevalent nonvascular findings in all of our CGD patients were white scaling ( N = 67%, 62.61%), diffuse or localized orange structureless areas ( N = 53%, 49.53%), and diffuse erythema ( N = 48%, 44.85%). Furthermore, the most frequent vascular findings in all of our CGD cases were branching and arborizing vessels ( N = 30%, 28.03%), linear irregular ( N = 30%, 28.03%), and dotted vessels ( N = 27%, 25.23%). Conclusion: For differentiating leishmaniasis from sarcoidosis by dermoscopy, white scaling and white scarring areas are more suggestive of cutaneous leishmaniasis, whereas the presence of arborizing vessels would be more in favor of sarcoidosis. When comparing GA to cutaneous leishmaniasis, the latter significantly shows more linear irregular vessels, hairpin vessels, white scaling, and white scarring areas. In the case of differentiating sarcoidosis from GA, the presence of hairpin vessels would be suggestive of sarcoidosis.